Separation of caffeoylquinic acids and flavonoids from Asteris souliei by high‐performance counter‐current chromatography and their anti‐inflammatory activity in vitro. Issue 10 (18th April 2017) - Zhang, Qiang; Pei, He‐Ying; Chen, Kai; Tang, Huan; Wu, Bo; Tang, Ming‐Hai; Peng, Ai‐Hua; Ye, Hao‐Yu; Chen, Li‐Juan
Abstract : Eleven compounds were successfully separated from Asteris souliei by using a two‐step high‐performance counter‐current chromatography method. The first step involved a reversed phase isocratic counter‐current chromatography separation using hexane/ethyl acetate/methanol/water (1:0.8:1:1 v/v/v/v), which produced three fractions, the first two of which were mixtures. The second step used step‐gradient reversed‐phase counter‐current chromatography with hexane/butanol/ethyl acetate/methanol/water (1:0.5:3.5:1:4 v/v/v/v/v) initially followed by hexane/ethyl acetate/methanol/water (1:2:1:2 v/v/v/v) to separate Fraction 1 into seven compounds; and hexane/ethyl acetate/methanol/water (1:1:1:1.2 v/v/v/v) to separate Fraction 2 into three further compounds. The chemical structures of the separated compounds were identified by ESI‐MS and NMR spectroscopy ( 1 H and 13 C). Baicalin (5 ), eriodictyol (7 ), apigenin‐7‐glycoside (8 ), quercetin (9 ), luteolin (10 ), and apigenin (11 ) showed obvious inhibitory effects on lipopolysaccharide‐induced nitric oxide production in RAW264.7 cells at a concentration of 10 μg/mL.